2018
DOI: 10.1177/0022487117751401
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood General and Special Educators: An Examination of Similarities and Differences in Beliefs, Knowledge, and Practice

Abstract: In this study, we provide a contemporary examination of the similarities and differences between early childhood general educators (ECEs) and early childhood special educators (ECSEs) within a theoretically driven model that accounted for the associations of beliefs and knowledge with practice. We used structural equation modeling to examine the associations among these multifaceted constructs, controlling for background characteristics, for 147 ECEs and 78 ECSEs. Univariate analyses revealed differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Previous research investigating both the knowledge of early childhood educators and the support for vocabulary development present in early childhood settings has indicated that both educator knowledge and enacted practice are less than optimal for supporting children's long‐term reading related outcomes (e.g., Piasta et al, ; Cash et al, ; Landry et al, ; Pelatti et al, ; Wright & Neuman, )—and that the relationship between the two is unclear (e.g, Carlisle et al, ; Hindman & Wasik, ; Pianta et al, ; Schachter et al, ; Spear et al, ). Our findings suggest that to develop a richer understanding of the relationship between knowledge and practice, it is important to uncover how early childhood educators are using the knowledge they hold in their moment‐to‐moment decision making.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research investigating both the knowledge of early childhood educators and the support for vocabulary development present in early childhood settings has indicated that both educator knowledge and enacted practice are less than optimal for supporting children's long‐term reading related outcomes (e.g., Piasta et al, ; Cash et al, ; Landry et al, ; Pelatti et al, ; Wright & Neuman, )—and that the relationship between the two is unclear (e.g, Carlisle et al, ; Hindman & Wasik, ; Pianta et al, ; Schachter et al, ; Spear et al, ). Our findings suggest that to develop a richer understanding of the relationship between knowledge and practice, it is important to uncover how early childhood educators are using the knowledge they hold in their moment‐to‐moment decision making.…”
Section: Resultsmentioning
confidence: 99%
“…The connection between measures of knowledge and children's outcomes is not conclusive. Some researchers have demonstrated associations between educators' knowledge and their enacted language and literacy practices (e.g., Hindman & Wasik, ; Schachter, Spear, Piasta, Justice, & Logan, ; Spear et al, ), whereas other studies have found no or minimal associations (e.g., Carlisle, Correnti, Phelps, & Zeng, ; Pianta et al, ). In addition, studies have shown variable associations between educators' knowledge and children's outcomes, in that knowledge only seems to predict a subset of child‐level skills (Cash et al, ; S.B.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…With the exception of those who attend blended ECE/ECSE educator preparation programs, ECE and ECSE teachers are generally prepared in vastly different ways, which impacts their professional development needs (Spear et al, 2018). ECE teachers have expressed concerns about their preparation to individualize instruction and teach children with more significant needs (e.g., Yu, 2019) while such skills are a focus of ECSE teacher preparation (Chandler et al, 2012).…”
Section: Blueprints For Inclusive Early Childhood Education: Applying An Expansive Conceptualization In Context-specific Waysmentioning
confidence: 99%
“…Much is inferred, for example, in studies of professional development which aim to improve knowledge and have subsequently identified effects on practice (Dickinson & Caswell, 2007;Wasik, Bond & Hindman, 2006). Studies which explicitly assess pedagogical language-andliteracy knowledge have identified small or null effects (Piasta, Park, Farley, Justice & O'Connell, 2020;Phillips, Oliver, Tabulda, Wood & Funari, 2020;Spear et al, 2018;Schachter et al, 2016). Such equivocality is puzzling, given the theoretical value of domain-specific pedagogical knowledge and evidence of its importance in later education phases, for example, in the domain of mathematics teaching (Baumert et al, 2010;McCray, 2008).…”
Section: The Role Of Teacher Knowledge and The Limits Of Current Resementioning
confidence: 99%